Answer:
we need a number line for this question...
Step-by-step explanation:
Answer:
3x-2
Step-by-step explanation:
JK =JL+LM
5x-8=JL +(2x -6)
JL = 5x-8 -2x+6
JL = 3x-2
Answer:
![6+\frac{i}{3}](https://tex.z-dn.net/?f=6%2B%5Cfrac%7Bi%7D%7B3%7D)
Step-by-step explanation:
![\frac{1}{3\imath}-(-6+\frac{2}{3\imath})](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%5Cimath%7D-%28-6%2B%5Cfrac%7B2%7D%7B3%5Cimath%7D%29)
![\frac{1}{3\imath}+6-\frac{2}{3\imath}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%5Cimath%7D%2B6-%5Cfrac%7B2%7D%7B3%5Cimath%7D)
taking like terms together
![\frac{1}{3\imath}-\frac{2}{3\imath}+6](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%5Cimath%7D-%5Cfrac%7B2%7D%7B3%5Cimath%7D%2B6)
taking LCM
![\frac{1-2}{3\imath}+6](https://tex.z-dn.net/?f=%5Cfrac%7B1-2%7D%7B3%5Cimath%7D%2B6)
![\frac{-1}{3\imath}+6](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B3%5Cimath%7D%2B6)
taking LCM
![\frac{-1+18\imath}{3\imath}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%2B18%5Cimath%7D%7B3%5Cimath%7D)
splitting the term
![\frac{-1+18\imath}{3\imath}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%2B18%5Cimath%7D%7B3%5Cimath%7D)
splitting the term
![-\frac{1}{3\imath}+\frac{18\imath}{3\imath}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%5Cimath%7D%2B%5Cfrac%7B18%5Cimath%7D%7B3%5Cimath%7D)
![-\frac{1\times3\imath}{3\imath \times \imath}+6](https://tex.z-dn.net/?f=-%5Cfrac%7B1%5Ctimes3%5Cimath%7D%7B3%5Cimath%20%5Ctimes%20%5Cimath%7D%2B6)
![-\frac{i}{3\imath^2}+6](https://tex.z-dn.net/?f=-%5Cfrac%7Bi%7D%7B3%5Cimath%5E2%7D%2B6)
we know that
![\imath^2=-1](https://tex.z-dn.net/?f=%5Cimath%5E2%3D-1)
putting this value in above equation
![\frac{\imath}{3}+6](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cimath%7D%7B3%7D%2B6)
10, 0, -10
You just have to subtract by 10